USE OF MICROCONTROLLER FOR MEASURING SHAFT SPEED OF DIESEL LOCOMOTIVE HYDRAULIC TRANSMISSION - Zhukovytskyy, I. V.; Kliushnyk, I. A. (Science and Transport Progress, 2016)
Purpose. The article considers the process of development and improvement of tachometer data collectors for the data-measuring diesel locomotive hydraulic transmission test system, which will give the possibility of obtaining the source data to conduct further studies of the technical condition of diesel locomotive hydraulic transmission. It is supposed to provide a solution to the problem of development and improvement of tachometer data measuring tools of the previously created data-measuring diesel locomotive hydraulic transmission test system, starting out from the possibility of modification of the existing locomotive hydraulic transmission test-bench at the Dnepropetrovsk Diesel Locomotive Repair Plant «Promteplovoz». Methodology. The researchers proposed in the work a method of modifying the existing tachometer sensor of the automated microprocessor system for the locomotive hydraulic transmission test-bench in the conditions of a diesel locomotive repair plant. It is applicable by substantiating the choice of the required tachometer sensor measuring method, as well as by using the necessary hardware and software to accomplish the goal with the ability to integrate into the data-measuring system for diesel locomotive hydraulic transmission testing. Findings. The available equipment of the locomotive hydraulic transmission test-bench allowed for design of the optical type speed sensor based on the existing sensor D-2MMU-2. The factory testing with the use of a sensor prototype resulted in determination of the required and sufficient sampling time for sensor operating microcontroller. Originality. The available equipment of the locomotive hydraulic transmission test-bench allowed for design of the optical type speed sensor based on the existing sensor D-2MMU-2. We developed the operation algorithms for the microcontroller that processes the signals from this sensor. The sensor was factory-tested. According to the data sample obtained during the tests, we showed the possibility of reducing the sensor information retrieval frequency. Practical value. The designed sensor significantly reduces the cost of development of the diesel locomotive hydraulic transmission test-bench, besides it can be used when developing similar hydraulic transmission test-benches of other wheeled vehicles and the like. The designed sensor has a greater accuracy than that of D-2-2MMU and considerably lower production cost in comparison with current tachometer sensors. The measurement results are input data to perform further studies in order to determine the technical condition of UGP750-1200 hydraulic transmission during the factory post-repair testing.